Ultrasonography of Swellings in Orofacial Region - Shivanand B Bagewadi; V G Mahima; Karthikeya Patil (Wolters Kluwer Medknow Publications, 2010)
Objectives: To assess the reliability of ultrasonography as a diagnostic aid for diagnosis of swellings in orofacial region. Study design: The study consisted of 40 patients with orofacial swellings, and all these patients were subjected to clinical, ultrasonographical and histopathological examination and respective diagnoses were obtained. Ultrasonographic diagnosis correlated with clinical and histopathological examinination. Chi-square test and contingency coefficient tests were used for statistical evaluation. Results: A significant association was observed between clinical and ultrasonographic diagnoses (contingency = 0.938 and p< 000) and between ultrasonographic and histopathological diagnoses (contingency = 0.943 and p< 000). Conclusion: Ultrasonography revealed as a valuable adjunct in the diagnosis of orofacial swellings.